Reframing Arabic Language Learning through Peer Teaching: A Constructivist Case Study of Student Learning Experience - Makhiulil Kirom; Mamluatul Hasanah; Miftahul Huda (UIN Syekh Wasil Kediri, Indonesia, 2026)
Although peer teaching has been widely examined as a collaborative learning strategy, relatively few studies have explored how it shapes students' learning experiences from a constructivist perspective within intensive Arabic language programs. This study examines the implementation of peer teaching and interprets how it shapes students' learning experiences within a constructivist learning framework. The study employed a descriptive case study at the Arabic Intensive Program (PKPBA), UIN Maulana Malik Ibrahim Malang, integrating a student perception questionnaire completed by 50 students with classroom observations as contextual evidence. Questionnaire data were analyzed descriptively using mean scores, while classroom observations were used to support the interpretation of the findings. The questionnaire indicated consistently positive student perceptions across the five measured constructs, with mean scores ranging from 3.45 to 3.60 on a five-point Likert scale, covering learning motivation, psychological safety, collaborative interaction, confidence in using Arabic, and reflective learning strategies. Classroom observations corroborated these descriptive findings and demonstrated how peer interaction encouraged students to negotiate meaning, participate more actively, and gradually assume greater responsibility for their own learning. The findings suggest that peer teaching functions as a constructivist learning practice that supports students' gradual shift from passive recipients of knowledge toward active learning agents. These findings provide practical implications for integrating peer teaching into Arabic language instruction and may also inform constructivist learning design in other second-language (L2) contexts. Abstrak Meskipun peer teaching telah banyak diteliti sebagai strategi pembelajaran kolaboratif, relatif sedikit studi yang mengeksplorasi bagaimana hal itu membentuk pengalaman belajar mahasiswa dari perspektif konstruktivis dalam program bahasa Arab intensif. Studi ini meneliti implementasi peer teaching dan menafsirkan bagaimana hal itu membentuk pengalaman belajar mahasiswa dalam kerangka pembelajaran konstruktivis. Studi ini menggunakan studi kasus deskriptif di Program Khusus Perkuliahan Bahasa Arab (PKPBA), UIN Maulana Malik Ibrahim Malang, dengan mengintegrasikan kuesioner persepsi mahasiswa yang diisi oleh 50 mahasiswa dengan observasi kelas sebagai bukti kontekstual. Data kuesioner dianalisis secara deskriptif menggunakan skor rata-rata, sementara observasi kelas digunakan untuk mendukung interpretasi temuan. Kuesioner menunjukkan persepsi siswa yang konsisten positif di kelima konstruk yang diukur, dengan skor rata-rata berkisar antara 3,45 hingga 3,60 pada skala Likert, yang mencakup motivasi belajar, keamanan psikologis, interaksi kolaboratif, kepercayaan diri dalam menggunakan bahasa Arab, dan strategi pembelajaran reflektif. Observasi kelas menguatkan temuan deskriptif ini dan menunjukkan bagaimana interaksi teman sebaya mendorong mahasiswa untuk menegosiasikan makna, berpartisipasi lebih aktif, dan secara bertahap memikul tanggung jawab yang lebih besar atas pembelajaran mereka sendiri. Temuan ini menunjukkan bahwa peer teaching berfungsi sebagai praktik pembelajaran konstruktivis yang mendukung pergeseran bertahap mahasiswa dari penerima pengetahuan pasif menuju agen pembelajaran aktif. Temuan ini memberikan implikasi praktis untuk mengintegrasikan pengajaran oleh teman sebaya ke dalam pengajaran bahasa Arab dan juga dapat memberikan informasi untuk desain pembelajaran konstruktivis dalam konteks bahasa kedua (L2) lainnya.